Judicial Investigation of Crime in Mid-Victorian Scotland - Shiels, Robert S. (Law, crime & history, 2024)
Modern reform of criminal procedure in Scotland abolished the competence of a judicial examination to obtain a declaration after an accused has been arrested. The ancient procedure, probably pre-reformation, of judicial examination had been common for centuries for serious crimes and required an accused to be taken before a judge at first instance, as examining magistrate, to be questioned at a private hearing. The reduction to writing of the voluntary and spontaneous responses of an accused to judicial inquiries were admissible evidence in any subsequent trial. The basic principles were set down in textbooks and were more than remnants of a quasi-inquisitorial procedure that worked well.